JOB COMMITMENT AMONG CIVIL SERVANTS IN UYO METROPOLIS - Imbur, Moses T.; Iloma, David O.; Obadimu, Clement O. (African Journal of Social and Behavioural Sciences, 2024)
Civil servants in Nigeria are believed to be among the least committed and appreciated categories of workers and they sometimes engage in shady dealings in order to meet up with societal expectations. Ensuring worker’s well-being prompted the researchers to investigate the role of workplace conflict and employee ability on job commitment among civil servants in Uyo metropolis. Two hundred (200) participants were purposively recruited from four government ministries at Idongesit Nkanga Secretariat in Uyo Local Government Area, consisting of 108 males and 92 females with ages ranging from 25 to 60 years and mean age of 40 years. In order to ascertain the determinants of job commitment, three standardized instruments were employed to collect data, namely: Organizational Commitment Questionnaire, Workplace Interpersonal Conflict Scale and Work-ability Support Scale. Two hypotheses were tested by utilizing statistical tools such as multiple regressions, and other descriptive statistics. The first hypothesis was not affirmed as workplace conflict was not an independent predictor of job commitment (β= -0.108; t = -1.580; P= >0.05). The second finding showed that employee ability was an independent predictor of employees’ commitment (β= 0.310; t = 4.510; P=<0.05). The study, however, found a joint influence of predictor variables on job commitment (F= (2,192) = 11.735; P<0.01), and concluded that training on managing workplace conflict and preventing escalation of tension coupled with adequately motivating employee’s ability will go a long way in eliciting appropriate job commitment and reducing associated risk of low performance and poor turnover intentions; while recommendations and suggestion for further studies were advanced.